2014
DOI: 10.1002/jlcr.3193
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [13C6]‐labelled phenethylamine derivatives for drug quantification in biological samples

Abstract: The availability of high-quality (13)C-labelled internal standards will improve accurate quantification of narcotics and drugs in biological samples. Thus, the synthesis of 10 [(13)C6]-labelled phenethylamine derivatives, namely amphetamine, methamphetamine, 3,4-methylenedioxyamphetamine, 3,4-methylenedioxymethamphetamine, 3,4-methylenedioxy-N-ethylamphetamine, 4-methoxyamphetamine, 4-methoxymethamphetamine, 3,5-dimethoxyphenethylamine 4-bromo-2,5-dimethoxyphenethylamine and 2,5-dimethoxy-4-iodophenethylamine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The Henry reaction is a well-established means of generating nitroalkenes. We found that sonication of the appropriate substituted benzaldehyde and nitroalkane partners in the presence of a butylamine catalyst in acetic acid produced the corresponding nitrostyrenes that were readily purified by either trituration with cold methanol or chromatography over a small silica pad using a toluene-based eluent . The reduction of these nitrostyrenes was performed using lithium aluminum hydride in most cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Henry reaction is a well-established means of generating nitroalkenes. We found that sonication of the appropriate substituted benzaldehyde and nitroalkane partners in the presence of a butylamine catalyst in acetic acid produced the corresponding nitrostyrenes that were readily purified by either trituration with cold methanol or chromatography over a small silica pad using a toluene-based eluent . The reduction of these nitrostyrenes was performed using lithium aluminum hydride in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…We found that sonication of the appropriate substituted benzaldehyde and nitroalkane partners in the presence of a butylamine catalyst in acetic acid produced the corresponding nitrostyrenes that were readily purified by either trituration with cold methanol or chromatography over a small silica pad using a toluene-based eluent. 16 The reduction of these nitrostyrenes was performed using lithium aluminum hydride in most cases. In cases where the 4-substituent was trifluoromethyl, iodo, bromo, or chloro, alane (aluminum hydride) formed in situ was instead used to prevent dehalogenation.…”
Section: Synthesis Of Ariadne and Its Analogs Majority Ofmentioning
confidence: 99%
“…The conversion is having 95 % yield and required continuous removal of methanol by toluene azeotrope. [41] Scheme 32. N-formylation of phenylalanine ethyl ester.…”
Section: Synthesis Of 13 C 6 Labelled 2-hydroxybenzaldehydementioning
confidence: 99%
“…In this process, ortho‐specific formylation has been done with the use of magnesium methoxide and formaldehyde (Scheme 35). The conversion is having 95 % yield and required continuous removal of methanol by toluene azeotrope [41] …”
Section: Formylation Of Phenolic Compoundsmentioning
confidence: 99%